Pengaruh Retribusi Daerah Terhadap Pendapatan Asli Daerah Kota Metro - Lyastyla, Lyastyla; Zanaria, Yulita; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine the contribution of regional levies and the level of effectiveness of regional levies in increasing Metro City's original regional income for 2020-2022. The type of research used is verification research. This research uses an explanatory survey research method. The instruments used in this research were interviews and observations. The data analysis carried out is Contribution Analysis and tax growth rate analysis. Contribution analysis is an analytical tool used to find out how much contribution can be made from Regional Distribution to Metro City's original regional income. The research results show that the level of effectiveness of Metro City Regional Distribution collection management during the 2020-2022 period can be said to be effective. The higher the effectiveness ratio, the better the regional distribution collection picture. Average contribution of Regional Distribution to Metro City Regional Original Income for the 2020-2022 period. This figure shows that the contribution of Regional Distribution to Original Regional Income is still not good.